Social Media and Religious Intolerance in Indonesia - Akhmad Rizal Shidiq; Burhanuddin Muhtadi; Arief Anshory Yusuf (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2026)
Indonesia has simultaneously experienced rapid growth in social media use and persistent concerns about rising religious intolerance, prompting widespread assumptions that digital platforms are fueling intolerance. Yet, the literature offers mixed predictions: social media may heighten hostility through echo-chamber dynamics, reduce prejudice through weak-tie intergroup contact, or generate little attitudinal change on religious tolerance. Drawing on these competing theoretical frameworks, we analyze a nationally representative survey of Indonesian Muslims (N = 3,820) to assess whether social media use for religious and political information is associated with higher levels of religious intolerance. From our econometric regression results, we do not find statistically significant evidence that Indonesian Muslims’ exposure to social media is correlated with higher level of religious intolerance. Our results suggest that in Indonesia—as in several other countries—social media may amplify the visibility of intolerant discourse without substantially shifting underlying attitudes.